Climate Action Innovation Hub: Innovators Booklet - African Union; AICCRA (2025)
The second Climate Action Innovation Hub, convened by the African Union (AU) during the 2025 Africa Climate Summit (ACS2) in Addis Ababa, served as a platform to showcase and scale African-led climate solutions. The Hub brought together 76 innovators from 32 countries whose enterprises address climate adaptation, mitigation and resilience across key thematic areas of the AU Climate Change and Resilient Development Strategy (2022–2032), including food systems, energy access, digital transformation, resilient water systems, sustainable urban development, mobility, industrialisation, and biodiversity protection. Through pitch sessions, high-level dialogues and partnership-building activities, innovators engaged policymakers, investors and development partners to highlight the enabling conditions required for scaling, including financing, market access, and supportive policy environments. A complementary post-Summit training programme further strengthened business and impact capabilities to enhance long-term viability and growth. This booklet profiles the innovators' work, demonstrating how African ingenuity is already shaping a climate-resilient, inclusive, and sustainable future.